A computational study of the low-lying electronic states of diatomic beryllium bismuthide. (November 2022) - Yu, Hong-Yang; Wang, Qing-Long; Wu, Jin-Peng; Hu, Zhuo-Jin; Jiang, Rong-Yao; Zhang, Chuan-Zhao; Jin, Yuan-Yuan; Chen, Shan-Jun; Li, Song
Highlights: High level computations with the inclusion of spin-orbit coupling are employed. Spectroscopic constants for the electronic states are obtained for the first time. Transition properties of the species are analyzed. Abstract: We have performed high-level ab initio computations to provide information associated with potential energy curves, molecular structures, electronic structures and vibrational energy levels of BeBi, which is yet an experimentally unknown species. Spectroscopic constants for twelve Λ-S states of the first four Λ-S dissociation channels are obtained for the first time. The feature of seven low-lying excited Ω states of BeBi, corresponding to the first three Ω dissociation limits, has been reported. The spin-orbit coupling effect is proved to have caused a significant impact on the investigated electronic states and interactions among them. Moreover, transition probabilities, such as transition dipole moments, Franck-Condon factors, Einstein coefficients, vibrational branching ratios and radiative lifetimes, are calculated for selected transition bands. Accompany computations are also been carried out for other Be-VA group diatomics of BeN, BeP and BeAs. Relevant data correlated with BeSb are collected from our previous study [ Spectrochim. Acta A 208 (2019) 124]. Regular tendencies associated with molecular structures and spectroscopic constants are demonstrated from BeN to BeBi. We expect this work will extend our knowledge of the Be-VA group species and satisfy demands for experimental detections on BeBi.